Verbally Induced Olfactory Illusions Are Not Caused by Visual Processing: Evidence From Early and Late Blindness. (May 2021) - Cornell Kärnekull*, Stina; Gerdfeldter, Billy; Larsson, Maria; Arshamian, Artin
Olfactory perception is malleable and easily modulated by top-down processes such as those induced by visual and verbal information. A classic example of this is olfactory illusions where the perceived pleasantness of an odor is manipulated by the valence of a verbal label that is either visually or auditorily presented together with the odor. The mechanism behind this illusion is still unknown, and it is not clear if it is driven only by verbal information or if there is an interaction between language functions and visual mental imagery processes. One way to test this directly is to study early blind individuals who have little or no experience of visual information or visual mental imagery. Here, we did this by testing early blind, late blind, and sighted individuals in a classical paradigm where odors were presented with negative, neutral, and positive labels via speech. In contrast to our hypothesis—that the lack of visual imagery would render early blind individuals less susceptible to the olfactory illusion—early and late blind participants showed more amplified illusions than sighted. These findings demonstrate that the general mechanism underlying verbally induced olfactory illusions is not caused by visual processing and visual mental imagery per se.